8 AJARAN MORAL SOSROKARTONO DARI PERSPEKTIF TEORI ETIKA DEONTOLOGISME - Mulyono, Mulyono (HUMANIKA, 2014)
Sosrokartono is a spectacular philosopher. He gave moral teachings as well as practicing the teachings consistently and consequently in his daily lives. Most of its moral teachings are deontological. Sosrokartono teaches that man in his life should fulfill its obligations. The obligation of human life is to love and devote ourselves to God, Al Khalik. The manifestation of obligation is to do something like help to fellow human being who need outright, with no strings attached (â€œleladi mring sesamiâ€). Central of Sosrokartonoâ€™s moral teachings is formulated in â€œIlmu Kantong Bolongâ€. Sosrokartonoâ€™s moral teachings are very relevant to address problems of demoralization that hit Indonesian society and the nation at this time, as the excesses of swift currents of globalization. Sosrokartonoâ€™s moral teachings, which emphasize concern for the fate of others, can eliminate attitudes that materialistic, invividualistic, secularistic, and hedonistic which is endemic.